Supply Chain Integration, Quality, and Knowledge Management in the Aerospace Industry - Gastélum-Valdez, Jesús Sigifredo; Valenzo-Jiménez, Marco Alberto; Martínez-Arroyo, Jaime Apolinar; González-Samaniego, Arcadio (Revista Venezolana de Gerencia, 2024)
In recent years, Supply Chain Integration (SCI) has gained attention in academic and empirical research. However, SCI has little consensus on conceptualizations, definitions, and dimensions. This research aims to analyze how quality management and knowledge management contribute to integrating the supply chain and participate in solving some of this misleading analysis of the aerospace industry in Queretaro, Mexico. To evaluate the influence of the variables, the structural equation modeling was used using the partial least squares approach (SEM-PLS). A census was made of the 48 firms in the aerospace industry through an interview with the firm’s executives. The model results show that knowledge management positively and significantly influences supply chain integration. Information and knowledge acquisition, both internally and externally, are essential for firms to improve their performance. Firms also must develop quality management systems that involve all the participants to integrate into global supply chains.